12.05: Global buckling behaviour of welded Q460GJ steel box columns: Experimental study and numerical simulations. (13th September 2017) - Zhou, Xiong; Kang, Shao‐Bo; Yang, Bo; Nie, Shi‐Dong
ABSTRACT: High‐performance structural steel has been widely used for columns in construction practices due to its significant advantages over conventional steel. However, the same design approach with conventional steel columns is still adopted in the design of high‐performance steel columns. As a result, its superior properties cannot be fully considered in design. This paper describes an experimental and numerical study on the global buckling behaviour of welded Q460GJ steel box columns. In the experimental programme, four steel columns with different cross sections and wall thicknesses were tested under axial compression. Comparisons were made between experimental results and design values calculated in accordance with national standards. Furthermore, numerical models were established in which material nonlinearity and residual stress distributions were considered. The model was validated against test data with reasonably good accuracy. Experimental and numerical results indicated that Q460GJ steel box columns could develop higher global buckling resistances than the values calculated from different standards. Therefore, it is necessary to modify the design approaches for conventional steel columns so that the buckling behaviour of box columns fabricated of Q460GJ steel can be accurately evaluated.